IPv6 Transition Measurements in LTE and VHT Wi-Fi Mobile Networks - Mina Malekzadeh (IEEE Access, 2019)
Full digital connectivity of the Internet of Things (IoT) devices demands several requirements including high-speed networks and a large number of IP addresses. The long term evolution (LTE) and very high throughput (VHT) 802.11ac networks are among the alternatives that can fulfill the speed requirements. To provide a large number of IP addresses, in addition to IPv4, LTE and 802.11ac also support IPv6. However, while the full digital connectivity cannot be fulfilled by IPv4 due to its limited address space and failure to support the scalability of the IoT applications, another major problem is that the potential benefits of IPv6 for LTE and 802.11ac mobile networks are completely ambiguous. The issue is further increased along with the design complexities inherent in LTE and 802.11ac infrastructures. Therefore, there are increasing concerns for cellular carriers and mobile service providers regarding migration to IPv6-only and whether the users in LTE-IPv6-only and 802.11ac-IPv6-only networks can achieve better performance than IPv4. To address the challenges associated with deploying IPv6-only in LTE and 802.11ac networks and quantify the performance, this work proposes a model. The model consists of a simulation environment with four distinct networks: LTE-IPv6-only, LTE-IPv4-only, 802.11ac-IPv6-only, and 802.11ac-IPv4-only. The model is further extended by setting up a real-world testbed environment to include four networks for replication of those simulations. To assure the most comprehensive environmental evaluation of the model, 128 distinct scenarios are developed and implemented, and the results are obtained in terms of quality of service parameters. The testbed results are compared to those of simulations to precisely assess the model.